FEDEX - INSTRUMENTUL INOVATOR DE STIMULARE Şl ÎNCURAJARE A INOVAŢIEI A FOST VALIDAT: IMPACTUL CIFRIC SOCIAL Şl PROFESIONAL - KULIKOVSKI, Conferențiar universitar , Lidia (BIBLIOPOLIS, 2020)
The author attempts to evaluate a new format, tested in 2014 at the B.P. Hasdeu Municipale Library - the format of ideas collected from the librarians, the format of stimulation of innovation in the institution, of education of innovation. The cantitative evaluation emphasizes the processus of joining, the hesitation of joining to the FedEx@Hasdeu in the library structures. The calitative evaluation highlights the benefices from the participation at the FedEx, the perceptual attitude of some librarians, especially managers. The author gives us a list of characteristics / factors that places FedEx@Flasdeu as tool of exploitation of librarians cognitive and creative surplus, that are not required in work.